Effect of pre-analytical treatments on bovine milk acute phase proteins - Thomas, Funmilola C.; Santana, Andre M. [UNESP]; Waterston, Mary; Haining, Hayley; Eckersall, Peter David (Springer Nature, 2016)
Background: Samples for diagnostic procedures often require some form of pre-analytical preparation for preservation or safe handling during transportation prior to analysis in the laboratory. This is particularly important for milk samples which frequently need preservatives to retain milk composition as close to that found in freshly collected samples as possible. Methods: Milk samples were treated by heating at 56 °C for 30 min or preserved by addition of either potassium dichromate or bronopol respectively. Haptoglobin (Hp), mammary associated serum amyloid A3 (M-SAA3) and C-reactive protein (CRP) were measured in the various treatment groups and in control samples which were not treated, using enzyme linked immunoassays. The concentrations of each APP were compared between treated and non-treated groups using the Wilcoxon signed ranks tests. Results: Heat treatment of samples was found to have a significant lowering effect on milk M-SAA3 and CRP but not Hp. The use of potassium dichromate and bronopol as preservatives in milk had no significant effects on milk Hp and M-SAA3 concentration but lowered milk CRP values compared to controls. Conclusions: The observed effects of heating and preservative use on milk APP should be taken into consideration when assaying samples which have undergone heat treatment as a result of international transfer regulations involving biological samples or samples needing chemical preservation prior to transport to laboratory.
Keywords: C-reactive protein; Haptoglobin; Mammary associated serum amyloid A3; Milk preservatives; Thermal stability